Trombólisis endovenosa en ACV isquémico: experiencia en un hospital de Popayán, Cauca - Anabeli Coronel Gaviria; Paulo Andrés Chilito; Carlos Ernesto Cabrera Velasco; Tomas Zamora Bastidas; Hernando Vargas Uricoechea (Acta Neurológica Colombiana, 2020)
INTRODUCCIÓN: